13 Effect of three types of information leaflets on intention to undergo diagnostic imaging for non-specific low back pain: a randomised controlled trial in patients and the general public. (4th December 2019) - Sharma, Sweekriti; Traeger, Adrian; O'Keeffe, Mary; Copp, Tessa; Freeman, Alexandra; Needs, Chris; Hoffman, Tammy; Richards, Bethan; Maher, Chris
Abstract : Background: Shared decision-making can reduce the uptake of some unnecessary tests and procedures. Although awareness of shared decision-making is increasing, overuse of diagnostic tests for common clinical conditions, such as low back pain, remains high. Recent public health campaigns, such as the 'Choosing Wisely' Initiative, attempt to persuade consumers to avoid unnecessary tests, rather than provide neutral information on benefits and harms. It is unclear whether persuasive information materials can influence perceptions of imaging tests more than neutral materials, and whether such public health approaches could have unintended consequences (e.g. decision regret). Objective: To evaluate the effect of different types of information leaflets on public perceptions of imaging for low back pain. Design: Randomised online experiment. Setting: Community (online) and 1 tertiary hospital. Participants: 360 members of the general public (recruited via Facebook) with or without low back pain, who have been asked to imagine they have experienced a severe episode of low back pain. Recruitment of the general public sample is due for completion in March 2019. We are also purposively sampling patients attending the back-pain outpatient clinic of a large tertiary hospital, who are being interviewed about the leaflets. Intervention: We are randomising participants to read one of the three leaflets on their computer screen, tablet, or smart phone: (i) Control leaflet: guideline information (ii) Neutral leaflet: balanced information on benefits/harms of imaging (iii) Persuasive leaflet: information biased towards harms of imaging. Immediately after reading the leaflet participants complete an online survey. Outcome measures: Intention to undergo imaging for low back pain (primary outcome measure). Secondary outcome measures include beliefs about necessity of imaging, usefulness of leaflet, knowledge, worry, harms, satisfaction with decision, decision regret. Results: The study is underway and due for completion in April 2019. We will present results in full at the conference. Conclusion: This study will be the first to compare the impact of information leaflets designed for a public health campaign about unnecessary imaging of low back pain. The data will inform future development of public health resources and shared decision-making interventions.